A fluorescence sedimentation assay for dsDNA antibodies. (18th August 2017) - Duus, K.; Draborg, A. H.; Güven, E.; Moreno, Y. M.; Jacobsen, S.; Nielsen, C. T.; Houen, G.
Abstract: The Farr assay is a radioimmunoassay (RIA) for dsDNA antibodies, based on antibody precipitation using ammonium sulphate and quantification using radio-labelled dsDNA. The RIA-Farr assay offers outstanding clinical specificity and sensitivity for systemic lupus erythematosus (SLE) compared to other assays but does also present some disadvantages as it utilizes radioactive-labelled dsDNA and requires high levels of technical expertise for safe handling. Here, a new precipitation assay, 'Fluoro-Farr' assay, is described. This assay maintains a high sensitivity and specificity for SLE but is based on precipitation with polyethylene glycol (PEG) and fluorescence of EvaGreen intercalated in dsDNA as detection principle. As dsDNA antibodies are quantified using fluorescence, the disadvantages of working with radioactivity are eliminated. The Fluoro-Farr assay was developed and validated, and the diagnostic efficiency of the assay was evaluated by testing 57 sera from SLE patients and 60 healthy controls. The Fluoro-Farr assay revealed a diagnostic sensitivity of 68% at a diagnostic specificity of 95% (ROC AUC 0.91). Furthermore, the new Fluoro-Farr assay was compared to the RIA-Farr assay, and showed a correlation of the outcomes from the two assays, but the Fluoro-Farr assay did not outperform the RIA-Farr assay due to its outstanding clinical diagnostic efficiency (ROC AUC 0.99). In conclusion, the Fluoro-Farr assay presents a viable alternative to the traditional RIA-Farr assay; especially in laboratories without facilities to perform assays with radioactivity-based read-out. As the RIA-Farr assay, the Fluoro-Farr assay has the advantage of being a precipitation assay allowing antibody:dsDNA interaction in solution using native dsDNA.